2014
DOI: 10.1111/isqu.12175
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Turnover and Foreign Policy Change: Societal Interests, Domestic Institutions, and Voting in the United Nations

Abstract: This study examines the effect of domestic political change on United Nations General Assembly (UNGA) voting. We argue that foreign policy change is most likely when a new leader-one who relies on different societal groups for support than her predecessor-comes to power. We then examine the extent that domestic institutional context-in particular, democracy-shapes this process. We test our hypotheses using a new measure of UNGA voting patterns and new data on changes in leaders' supporting coalitions. We find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(45 citation statements)
references
References 41 publications
2
42
0
1
Order By: Relevance
“…With some exceptions (Voeten 2000(Voeten , 2004Reed et al 2008;Mattes, Leeds, and Carroll 2015;Andersen, Harra, and Tarp 2006), spatial theory and IRT models have not been applied to the UN. One reason is that standard software packages for ideal point estimation do not easily incorporate votes with three choices.…”
Section: Literature Data and Methodsmentioning
confidence: 99%
“…With some exceptions (Voeten 2000(Voeten , 2004Reed et al 2008;Mattes, Leeds, and Carroll 2015;Andersen, Harra, and Tarp 2006), spatial theory and IRT models have not been applied to the UN. One reason is that standard software packages for ideal point estimation do not easily incorporate votes with three choices.…”
Section: Literature Data and Methodsmentioning
confidence: 99%
“…Firstly, how changes in leadership on both sides impact such results. Recent findings have shown that foreign policy patterns at the UNGA emanating from democratic countries remain fairly consistent and stable over time (Mattes, Leeds and Carroll 2015). On the inverted spectrum, leader turnover in autocratic countries is likelier to lead to more acute shifts in such a venue (Smith 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Focusing on the UNGA has several advantages: data availability is generally very high because all sovereign countries have voting rights. Votes in the UNGA furthermore cover a wide array of issues that allow to proxy general alignment tendencies instead of ad hoc political liaisons (Mattes et al, 2015). Voting alignment has thus often been used to proxy political closeness.…”
Section: Data and Operationalizationmentioning
confidence: 99%
“…Accordingly, UNGA voting patterns have frequently been used to proxy for political closeness between countries (e.g., Thacker, 1999;Barro and Lee, 2005;Bailey et al, 2015). Indeed, studies suggest that changes in heads of executive make a decisive difference when it comes to foreign policy proximity (Dreher and Jensen, 2013;Mattes et al, 2015). Yet, research has focused exclusively on either leadership changes in recipient countries only, or monadic position changes.…”
Section: Introductionmentioning
confidence: 99%